Генетичні особливості дифузного нетоксичного зоба у підлітковому віці - Багацька, Н. В.; Дємєнкова, І. Г.; Глотка, Л. І. (Clinical Endocrinology and Endocrine Surgery, 2010)
To find out the role of genetic factors in formation of nontoxic diffuse goiter in adolescence there were carried out clinico-genealogic, immunogenetic and dermatoglyphic investigation of probands of both sex. In-family accumulation of multilateral diseases was established in the relatives of I to III degree of consanguinity. Some peculiarities were revealed the incidence of distribution of class I antigens of the HLA system and in dermatoglyphic characters in the persons examined.